Littoral-cell angioma of the spleen: a case report - Dongming Liu; Zhaohui Chen; Tongtong Wang; Baichang Zhang; Hongyuan Zhou; Qiang Li (Cancer Biology & Medicine, 2017)
Littoral-cell angioma (LCA), a primary angioma which clinically belongs to splenic hemangioma, can be mostly found in normal spleen red sinus shore cells of reticuloendothelial cell system. The cells of LCA strongly express endothelial and tissue cell associated antigens that indicate a dual differentiation characteristic; whereas only endothelial cell markers are positive in normal spleen red sinus shore cells. Diagnosis of LCA relies on histopathology. Regular follow-up is needed to monitor recurrence and metastasis.